2020
DOI: 10.3390/ijms21093164
|View full text |Cite
|
Sign up to set email alerts
|

Leukamenin E Induces K8/18 Phosphorylation and Blocks the Assembly of Keratin Filament Networks Through ERK Activation

Abstract: Leukamenin E is a natural ent-kaurane diterpenoid isolated from Isodon racemosa (Hemsl) Hara that has been found to be a novel and potential keratin filament inhibitor, but its underlying mechanisms remain largely unknown. Here, we show that leukamenin E induces keratin filaments (KFs) depolymerization, largely independently of microfilament (MFs) and microtubules (MTs) in well-spread cells and inhibition of KFs assembly in spreading cells. These effects are accompanied by keratin phosphorylation at K8-Ser73/S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 52 publications
1
1
0
Order By: Relevance
“…In readdressing blood draws from patient PC1, using a combination of WGS, morphometrics and targeted proteomics, we found that copy number-neutral CK+ cells were morphologically distinct from clonal CTCs, had a high expression of the endothelial marker CD31, indicating an endothelial cell lineage (Figures 4 and 5) and, further, trended toward a lower CK signal (CKdim) than the clonal cells. Endothelial cells, despite their mesodermal origin, have been reported to express certain CKs such as CK7, CK1, CK8 and CK18, explaining why they can be found using a pan-CK-based rare-cell detection assay [40][41][42][43][44]. Consistent with that result, we have shown that both spiked endothelial cell lines as well as MI CECs were robustly detected using CK and Vim as inclusion and CD45 as exclusion markers.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In readdressing blood draws from patient PC1, using a combination of WGS, morphometrics and targeted proteomics, we found that copy number-neutral CK+ cells were morphologically distinct from clonal CTCs, had a high expression of the endothelial marker CD31, indicating an endothelial cell lineage (Figures 4 and 5) and, further, trended toward a lower CK signal (CKdim) than the clonal cells. Endothelial cells, despite their mesodermal origin, have been reported to express certain CKs such as CK7, CK1, CK8 and CK18, explaining why they can be found using a pan-CK-based rare-cell detection assay [40][41][42][43][44]. Consistent with that result, we have shown that both spiked endothelial cell lines as well as MI CECs were robustly detected using CK and Vim as inclusion and CD45 as exclusion markers.…”
Section: Discussionsupporting
confidence: 86%
“…Our earlier results on the prostate cancer index patient (PC 1) showed that single-cell copy-number profiling of rare CK+ cells could distinguish clonally altered tumor cells (CTCs) from cells of an uncertain origin displaying neutral genomes, and, further, that both populations varied according to the state of the disease [40][41][42][43][44]. The data presented here take this observation further and demonstrate that through a combination of epithelial, mesenchymal, endothelial, and leukocyte markers, it is possible to further discriminate multiple cell types within the population of rare CK+ circulating cells.…”
Section: Discussionmentioning
confidence: 99%